2017
DOI: 10.1186/s40066-017-0145-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of food security and consumption patterns among smallholder livestock farmers in Botswana

Abstract: Background: Achievement of food security is an important objective in the National Development Plan of Botswana. This study set out to characterise food security situation and food consumption patterns among livestock keepers in Botswana. The study also sought to determine the effect of various factors (including livestock-related issues) on nutrition/food consumption patterns of livestock farmers in Botswana. Data used in this study come from a survey of smallholder livestock producers conducted by the Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…It is known that food availability and food accessibility are the indicators of food security that depict the situation of farm household, while food consumption is the indicator of direct impact of food security, reflected by the quantity and quality of farm household food consumption. The result found that significant relationship was found 78.78 % (Table 2) between household food security, food consumption pattern and exogenous variables (household size, access to food family expenditure, energy consumption (Novianto et al, 2015), and protein consumption (Bahta et al, 2017).…”
Section: Level Of Household Food Securitymentioning
confidence: 97%
“…It is known that food availability and food accessibility are the indicators of food security that depict the situation of farm household, while food consumption is the indicator of direct impact of food security, reflected by the quantity and quality of farm household food consumption. The result found that significant relationship was found 78.78 % (Table 2) between household food security, food consumption pattern and exogenous variables (household size, access to food family expenditure, energy consumption (Novianto et al, 2015), and protein consumption (Bahta et al, 2017).…”
Section: Level Of Household Food Securitymentioning
confidence: 97%
“…(26,27). For example, implementation of a backyard garden project within the Ramotswa area in Botswana was able to successfully reduce poverty in participating households from 52-15% (28). Similar practices could be adopted and evaluated to strengthen agricultural practices in the Popokabaka area, with the aim of improving dietary diversity and alleviating poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike South Africa, which is food secure at the national level, Botswana is highly dependent on food imports, mainly because 70% of its total land comprises the Kalahari Desert. Botswana imports approximately 90% of its gross food supply from South Africa (Bahta et al, 2017). The same publication reveals that approximately 3500 square kilometers on the eastern and northern margins of Botswana is reported to be suitable for crop and livestock farming which is pursued by smallholder livestock producers.…”
Section: Figure 1 Map Showing Study Area Sitesmentioning
confidence: 99%